Tongan translation realities across Tā ('Time') and Vā ('Space'). Issue 2 (1st October 2019) - Kalavite, Telesia
AbstractThe kingdom of Tonga known as the Friendly Islands is a bilingual country where the official languages are Tongan (lea faka-Tonga) and English (lea faka-Pilitānia). In a bilingual environment like Tonga, the ability to translate effectively between the two languages is a fundamental skill to communicate well and to achieve academic success. The main focus of this article is to approach translation through a sociocultural lens, and more specifically, through a Tongan-inspired tāvāist perspective: 'Okusitino's Māhina's Tā‐Vā ('Time‐Space') Theory of Reality. This theory has influenced a range of practices from many disciplines and social activities, such as translation. Theorizing translation in and across Tā ('time') and Vā ('space') informs the relationships between languages, cultures and educational backgrounds in the transmission of 'ilo ('knowledge') and poto ('skills') among all members of the society. In exploring the theory this article will consider two translation case studies of English to Tongan literature: Lewis Carroll's Alice in Wonderland (1865) and Antoine de Saint-Exupéry's The Little Prince (1943).